2011
DOI: 10.1029/2011gc003508
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional model of an ultramafic feeder system to the Nikolai Greenstone mafic large igneous province, central Alaska Range

Abstract: [1] The Amphitheater Mountains and southern central Alaska Range expose a thick sequence of Triassic Nikolai basalts that is underlain by several mafic-ultramafic complexes, the largest and best exposed being the Fish Lake and Tangle (FL-T) mafic-ultramafic sills that flank the Amphitheater Mountains synform. Three-dimensional (3-D) modeling of gravity and magnetic data reveals details of the structure of the Amphitheater Mountains, such as the orientation and thickness of Nikolai basalts, and the geometry of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Given their close ages, these repeated disruptions in the carbon cycle could have been related to the emplacement of large masses of volcanic rocks from an igneous province. The Wrangellia LIP, also called the Nikolai LIP (Schmidt and Rogers, 2007;Greene et al, 2010;Glen et al, 2011), is indicated as the most important contributor, possibly strengthened by other basaltic and acidic volcanic sources, namely the South Taimyr igneous complex in Siberia plus the Kara Dere-Sayrun unit of the middle Antalya nappes and the Huglu-Pindos volcanics in Turkey (Dal Corso et al, 2012;Mueller et al, 2016a;Sun et al, 2016;Miller et al, 2017).…”
mentioning
confidence: 99%
“…Given their close ages, these repeated disruptions in the carbon cycle could have been related to the emplacement of large masses of volcanic rocks from an igneous province. The Wrangellia LIP, also called the Nikolai LIP (Schmidt and Rogers, 2007;Greene et al, 2010;Glen et al, 2011), is indicated as the most important contributor, possibly strengthened by other basaltic and acidic volcanic sources, namely the South Taimyr igneous complex in Siberia plus the Kara Dere-Sayrun unit of the middle Antalya nappes and the Huglu-Pindos volcanics in Turkey (Dal Corso et al, 2012;Mueller et al, 2016a;Sun et al, 2016;Miller et al, 2017).…”
mentioning
confidence: 99%
“…Intrusions of this scale (several 10's to several 100's of kilometers in diameter) compare in size to some of the largest mafic-ultramafic intrusions globally, some of which are known Ni-Cu-PGE producers. Some examples include the 50 km wide, 17-19 km thick Freetown igneous complex in Sierra Leone (Mgbatogu et al 1987), the > 30 km wide and 1.5 km thick Fish-Lake and Tangle mafic-ultramafic sills of the Nikolai Greenstone portion of the Wrangellia LIP (Glen et al 2011), and the 500 km wide, 7-9 km thick Rustenburg layered suite of the Bushveld intrusion (e.g. Cawthorn 1996).…”
Section: R a F T 4 Implications Of Our Modellingmentioning
confidence: 99%
“…For instance, these intrusions compare in size to some of the largest mafic-ultramafic intrusions around the globe, some of which are known Ni-Cu-PGE producers. Some examples include the 50 km wide, 17-19 km thick Freetown igneous complex in Sierra Leone (Mgbatogu et al, 1987), the > 30 km wide and 1.5 km thick Fish-Lake and Tangle mafic-ultramafic sills of the Nikolai Greenstone mafic LIP (Glen et al, 2011), and the 500 km wide, 7-9 km thick Rustenburg layered suite of the Bushveld intrusion (e.g. Cawthorn 1996).…”
Section: General Observations From Modellingmentioning
confidence: 99%